2008
DOI: 10.1055/s-0028-1083202
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ethyl Pyrimidine-4-carboxylates from Unsymmetrical Enamino Diketones and Their Application in the First Synthesis of Pyrimido[4,5-d]pyridazin-8(7H)-ones

Abstract: The reaction of unsymmetrical enamino diketones [RC(O)C(=CNMe 2)C(O)CO 2 Et, where R = Ph, 4-MeC 6 H 4 , 4-MeOC 6 H 4 , 4-BrC 6 H 4 , 4-ClC 6 H 4 , 4-FC 6 H 4 , 4-O 2 NC 6 H 4 , 2-thienyl, benzofuran-2-yl, and CF 3 ] with N-C-N dinucleophiles, such as benzamidine hydrochloride or 1H-pyrazole-1-carboxamidine monohydrochloride, afforded a series of ethyl 2,5-disubstituted pyrimidine-4-carboxylates in a chemoselective and highly chemoselective manner (51-86%). Reaction of these two series of pyrimidines (R = Ph, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Appropriately functionalized heterocycles can also lead to the formation of polyazaheterocycles. Our research group has reported the synthesis of ethyl 5-carbonylpyrimidine-4-carboxylates from unsymmetrical enaminodiketones and amidines and their application in the preparation of pyrimido[4,5- d ]pyridazin-8(7 H )-ones [8]. One of the most common approaches used for the synthesis of pyrazinones [910] and quinoxalinone [1112] cores is the cyclocondensation reaction between 1,2-dicarbonyl compounds and 1,2-diamines.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriately functionalized heterocycles can also lead to the formation of polyazaheterocycles. Our research group has reported the synthesis of ethyl 5-carbonylpyrimidine-4-carboxylates from unsymmetrical enaminodiketones and amidines and their application in the preparation of pyrimido[4,5- d ]pyridazin-8(7 H )-ones [8]. One of the most common approaches used for the synthesis of pyrazinones [910] and quinoxalinone [1112] cores is the cyclocondensation reaction between 1,2-dicarbonyl compounds and 1,2-diamines.…”
Section: Introductionmentioning
confidence: 99%